Probiotic Potential and Enhanced Adhesion of Fermented Foods-Isolated Lactic Acid Bacteria to Intestinal Epithelial Caco-2 and HT-29 Cells - Eun Ah Sim; Seon-Young Kim; SangNam Kim; Eun-Gyung Mun (Microorganisms, 2024)
This study evaluated the probiotic potential of lactic acid bacteria (LAB) isolated from fermented milk and soymilk products purchased from local markets. The LAB strains were assessed for acid and bile resistance, antibiotic resistance, and adhesion to human intestinal epithelial models. Streptococcus thermophilus (JAMI_LB_02) and Lactiplantibacillus plantarum (JAMI_LB_05) showed the highest survival rates in artificial gastric and bile juices, at 87.17 ± 0.02% and 96.71 ± 4.10%, respectively, with all strains (except JAMI_LB_03) demonstrating antibiotic resistance. Adhesion ability indicated the superior performance of JAMI_LB_02 and JAMI_LB_05 compared to standard strains. JAMI_LB_02 adhered to Caco-2 cells at 2.10 ± 0.94% and to HT-29 cells at 3.32 ± 0.38%, exceeding standard strains (1.06 ± 0.13% and 1.89 ± 0.58%). JAMI_LB_05 achieved the highest rates at 5.62 ± 1.33% on Caco-2 and 5.76 ± 0.46% on HT-29 cells. Their combination (JAMI_LB_02 + JAMI_LB_05) significantly enhanced adhesion to 18.57 ± 5.49% on Caco-2 and 21.67 ± 8.19% on HT-29 cells, demonstrating strong synergy. These findings highlight the probiotic potential of the isolated LAB strains, particularly in mixed formulations, which may improve intestinal survival, adaptability, and efficacy. Further in vivo studies are warranted to validate their clinical applications and optimize strain combinations for human health benefits.